Anti-Inflammatory Compounds from Vietnamese Piper bavinum - Viet Dung Hoang; Phi Hung Nguyen; Minh Thu Doan; Manh Hung Tran; Nhu Tuan Huynh; Huu Tung Nguyen; Byung Sun Min; Dao Cuong To (Journal of Chemistry)
This study reports the anti-inflammatory activity-guided fractionation of the aerial part of Piper bavinum C. CD. (Piperaceae) that led to the isolation of eight secondary metabolites (1–8). The chemical structures of 1–8 were established mainly by NMR and mass spectra. Compound 5 was isolated from P. bavinum for the first time. All the isolated compounds were evaluated against LPS-induced NO production in macrophage RAW 264.7 cells in vitro. Among them, compound 4 showed the most potent inhibitory activity against the LPS-induced NO production with an IC50 value of 5.2 μM followed by compound 5 that inhibited NO production with an IC50 value of 13.5 μM. In the protein levels, compound 4 suppressed LPS-induced COX-2 and iNOS expressions in a dose-dependent manner. The results suggested that P. bavinum and its constituents might exert anti-inflammatory effects.